Coal River - Wiseman, Ellen Marie (New York, NY : Kensington Books, 2015)
"In this vibrant new historical novel, the acclaimed author of The Plum Tree and What She Left Behind explores one young woman's determination to put an end to child labor in a Pennsylvania mining town."-- Provided by publisher.
"A novel"--Cover.
Includes discussion questions.
Keywords: Orphans -- Fiction; Child labor -- Fiction; Poor -- Fiction; Miners -- Fiction; Pennsylvania -- Fiction